Performance of Mulching to the Stimulation on the Growth of Cucumber (Cucumis Sativus) Production - Akter, Daliya; Islam, Mohammad Shafiqul; Ruhi, Roksana Aftab; Joy, Md Istiak Hossain; Trina, Fariha Ahmed (Bangladesh Journal of Multidisciplinary Scientific Research, 2020)
A field experiment was conducted at Noakhali ,Chittagong during the season in 2019, to determine the effect of mulching on cucumber (Cucumis sativus) production where Alavy Green variety was used. The study was laid out in RCBD (Randomized complete block design) method having three replications. The treatment used in this study consists of T1=Black plastic mulching, T2=Water hyacinth mulching, T3=Rice straw mulching, Control= no mulching. The plant showed significant differences after application of various treatments. The maximum average length of vine (113 cm), number of branch per plant (8.33), number of leaves per plant (28.44), number of tendrils per plant (11.52), number of flowers per plant (16.33), number of fruits per plant (9), length of fruit (18 cm), weight of individual fruit (239.67 g) were obtained from T1 treatment (Black plastic mulching) .On the other hand, minimum average length of vine (103.91 cm), number of branch per plant (4.33), number of leaves per plant (22.67), number of tendrils per plant (7.33), number of flowers per plant (12.33), number of fruits per plant (4.33), length of fruit (9 cm), weight of individual fruit (173.67 g) were obtained from T0 control (No mulching). Among organic (Water hyacinth and Rice straw) and inorganic mulches (Black plastic), inorganic mulches gave better performance over organic mulches.